Corruption and political institutions in Portugal: an exploratory analysis - Mendes, Silvia M. (2005)
Corruption, political cover-ups, and fraud in a general form have become a matter of political debate in the last few years in Portugal. It is not that corrupt politicians and government officials were not around before the 21st century and are only now abusing their public authority, but is it only now coming out in public and in a big way. After thirty years of democracy, Portuguese public misuse of power is apparently no longer tolerated for government officials suspected of fraud and corruption now are being formally charged. The literature on corruption and democracy indicate that this is a positive sign of progress in the democratic development of sound political institutions. Empirical studies are few and recent, but they generally tend to point to a negative effect of corruption on attitudes toward government. In Portugal, however, despite public knowledge of alleged events, citizens do not seem to assign any blame. In fact, perceptions of corruption and fraud do not always seem to affect citizens’ ropensity to trust in political institutions. Using surveys conducted by the Eurobarometer in Portugal, we explore the relationship between corruption and fraud and political trust in different political institutions. We find that this relationship varies depending upon the institution. Citizens with a greater perception and concern for corruption and fraud in general express lower levels of trust in government and in the justice system. Results also show that this relationship does not hold in the case of the parliament, political parties, and the police.